New aesthetics. Older poetics Approach to the trace of the influence of painting into the image - Irala-Hortal, Pilar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2017)
Throughout history, photography and painting advance together and, in most cases, especially in the first decades, they intersect and influence each other. The influence of photography on painting in the last third of the 19th century and vice versa has been studied from different perspectives. Also in the 21st century, photography looks again at the great painters of art history to inspire themselves, look for models, create metaphors and, ultimately, look at the roots of visual creation for the creative and aesthetic path to follow. In this article we expose some examples.